PATHOGENIC MICROORGANISMS (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
Pathogen is a general term for microorganisms and parasites that can cause disease. Parasites include mainly protozoa and worms, and the majority of microorganisms include viruses, chlamydia, rickettsia, mycoplasma, spirochetes, and fungi. There are more than 400 types of microorganisms that can infect a person, they are mainly distributed in the mouth, nose, throat and digestive organs of a person.